Avaliação da limpidez das placas de aço ultrabaixo carbono no início de operação do distribuidor do lingotamento contínuo. - Sérgio Roberto Lopes Moreira (2019)
The inclusions level present in the liquid steel interferes directly in the slabs quality produced by continuous casting, and are are determinant in surface defects formation in cold rolled products. The steel reoxidation, as well as the slag carried from the tundish to the mold, the interaction of the steel with tundish covering powder and mold flux powder, have a strong influence on the slabs cleanliness originated in solidification process in the mold. In the present work, the inclusions formed during the beginning of the continuous casting process for ultra-low carbon steels were evaluated under three different tundish cover powder addition conditions: Test 1; Test 2 and Test 3, in addition to the condition called Reference. The objective of the study was to reduce the amount of inclusions present and, consequently, the surface defects in the initial slabs, through the relation between itself and the oxygen content in the continuous casting machine. Such research will information for changes in the process conditions to improve the quality of the final product. In Test 1, the cover powder was added close to 17 t of molten steel in tundish, without an extended shroud, favoring reoxidation and emulsification. In Test 2, the cover powder was added with 22 t of molten steel in tundish, there were Al2O3-based inclusions, although with lower values compared to the 28 to 17 t moments (without extended shroud). In Test 3, the cover powder was added in tundish close to 17 t, with a 200 mm extension on the shroud, by the moment the molten steel is already stabilized. Not detected by this case, some surface defect caused by reoxidation.